Hepatoprotective effect of Cinnamon (Cinnamomum burmanii) extract on Serum Aspartate Transaminase (AST) of male wistar rats induced with isoniazid - Sovia, Evi; Kristiana, Ris; Nurdina, Salsabila; Rachman, Hidayatul (ACTA Medical Health Sciences, 2024)
Hepatotoxicity is a condition of liver cell damage that is often caused by drugs such as isoniazid. Isoniazid (INH) is an anti-tuberculosis drug that, when used excessively, can cause an increase in Reactive Oxygen Species (ROS) and trigger oxidative stress, thereby inducing cell necrosis, especially in the liver. Cinnamon is a plant that contains flavonoids, tannins, alkaloids, and essential oils, which are useful as antioxidants and have the potential hepatoprotective properties. This study aims to determine the effect of ethanol extract of cinnamo n (Cinnamomum burmanii) and its effective dose as hepatoprotection on aspartate transaminase (AST) levels in isoniazid-induced male rats. Extract preparation was carried out using the maceration method. This study was a post-test only control group design laboratory experiment with a sample of 25 male Wistar rats consisting of five groups: the normal control group was given aquabidest (K1), the positive control was induced with 200 mg/kg isoniazid (K2), and three treatment groups were induced with 200 mg/kg isoniazid and given cinnamon ethanol extract at a dose of 100 mg/kg BW, 200 mg/kg BW and 400mg/kg BW for 14 days. At the end of the study, the AST levels were measured. Data were analyzed using the One -Way Anova test and the Tukey's Post Hoc Test. The results showed that the ALT levels of the group given cinnamon at doses of 100, 200, and 400 mg/kg decreased significantly (p<0.05) by 93,20 ± 8,55, 85,60 ± 8,23, and 71,20 ± 3,56 U/L, respectively. The cinnamon ethanol extract could prevent increases in isoniazid-induced AST in rats, thus having a hepatoprotective activity. DOI : 10.35990/amhs.v2n3.p109-115 REFERENCES Lei, S., Gu, R., & Ma, X. (2021). Clinical perspectives of isoniazid-induced liver injury. Liver Research, 5(2), 45–52. https://doi.org/10.1016/j.livres.2021.02.001 Juliarta, I. G., Mulyantari, N. K., & Yasa, I. W. P. S. (2018). Gambaran hepatotoksisitas (ALT/AST) penggunaan obat antituberkulosis lini pertama dalam pengobatan pasien tuberkulosis paru rawat inap di RSUP Sanglah Denpasar tahun 2014. E-Jurnal Medika, 7(10), 1–10. Banjuradja, I., & Singh, G. (2020). Mekanisme hepatotoksisitas dan tatalaksana tuberkulosis pada gangguan hati. Indonesian Journal of Chest, 7(2), 55–64. Sumantri, A. F., Djumhana, A., Wisaksana, R., & Sumantri, R. (2015). Insidensi dan karakteristik hepatotoksisitas obat antituberkulosis pada penderita tuberkulosis dengan dan tanpa infeksi HIV. Global Medical and Health Communication, 3(2), 78. https://doi.org/10.29313/gmhc.v3i2.1548 Santoso, S. B., Chabibah, P. U., & Pribadi, P. (2021). Hepatotoxicity risk profile of Indonesian due to polymorphism of NAT2 and CYP2E1 in isoniazid metabolism. Urecol Journal Part D: Applied Science, 1(1), 9–16. Wang, P., Pradhan, K., Zhong, X. B., & Ma, X. (2016). Isoniazid metabolism and hepatotoxicity. Acta Pharmaceutica Sinica B, 6(5), 384–392. https://doi.org/10.1016/j.apsb.2016.07.014 Nahid, P., & Hopewell, P. C. (2016). Tuberculosis treatment. In International Encyclopedia of Public Health (Vol. 43(5), pp. 267–276). https://doi.org/10.1016/B978-0-12-803678-5.00473-2 Błaszczyk, N., Rosiak, A., & Kałużna-Czaplińska, J. (2021). The potential role of cinnamon in human health. Forests, 12(5), 1–17. https://doi.org/10.3390/f12050648 Rasydy, L. O. A., Supriyanta, J., & Novita, D. (2019). Formulasi ekstrak etanol 96% daun sirih hijau (Piper betle L.) dalam bedak tabur anti jerawat dan uji aktivitas antiacne terhadap Staphylococcus aureus. Jurnal Farmagazine, 6(2), 18. https://doi.org/10.47653/farm.v6i2.142 Rahayu, L., Yantih, N., & Supomo, Y. (2018). Analisis SGPT dan SGOT pada tikus yang diinduksi isoniazid untuk penentuan dosis dan karakteristik hepatoprotektif air buah nanas (Ananas comosus L. Merr) mentah. Jurnal Ilmu Kefarmasian Indonesia, 16(1), 100–106. Ifeanyi, O. E. (2018). A review on free radicals and antioxidants. International Journal of Current Research in Medical Sciences, 4(2), 123–133. https://doi.org/10.2174/22123989oteznmziwtcvy Singh, D., Cho, W. C., & Upadhyay, G. (2016). Drug-induced liver toxicity and prevention by herbal antioxidants: An overview. Frontiers in Physiology, 6(JAN), 1–18. https://doi.org/10.3389/fphys.2015.00363 Metushi, I., Uetrecht, J., & Phillips, E. (2016). Mechanism of isoniazid-induced hepatotoxicity: Then and now. British Journal of Clinical Pharmacology, 81(6), 1030–1036. https://doi.org/10.1111/bcp.12885 Maliangkay, O. J., Assa, Y., & Tiho, M. (2020). Kadar serum glutamic oxaloacetic transaminase (SGOT) pada peminum minuman beralkohol di Kelurahan Tosuraya Selatan. Jurnal e-Biomedik, 8(1), 120–126. Rafita, I. D., Lisdiana, & Marianti, A. (2016). Pengaruh ekstrak kayu manis terhadap gambaran histopatologi dan kadar SGOT-SGPT hepar tikus yang diinduksi parasetamol. Life Science, 4(1), 29–37. Antasionasti, I. J. (2021). Aktivitas antioksidan ekstrak etanol kayu manis (Cinnamomum burmani) secara in vitro. Jurnal Farmasi Udayana, 10(1), 38. https://doi.org/10.24843/jfu.2021.v10.i01.p05 Panche, A. N., Diwan, A. D., & Chandra, S. R. (2016). Flavonoids: An overview. Journal of Nutritional Science, 5(e47), 1–15. https://doi.org/10.1017/jns.2016.41 Hanifa, D. D., & Hendriani, R. (2016). Tanaman herbal yang memiliki aktivitas hepatoprotektor. Farmaka, 14(4), 43–51. Lestari, T., Lubis, Y. M., Nasution, S. W., et al. (2019). Uji efektivitas ekstrak buah kurma (Phoenix dactylifera) dan ekstrak buah mahkota dewa (Phaleria macrocarpa) sebagai nefroprotektor terhadap tikus yang diinduksi paracetamol. Jurnal Farmasi, 1(1), 8–15. Lagarde, F., Beausoleil, C., Belcher, S. M., et al. (2015). Non-monotonic dose-response relationships and endocrine disruptors: A qualitative method of assessment. Environmental Health, 14(1), 13. https://doi.org/10.1186/1476-069X-14-13